Anterior Cruciate Ligament Reconstruction with 4-Strand Hamstring Tendon Construct May be Biomechanically Superior to 5-Strand Hamstring Tendon Construct When Using Femoral Suspensory Fixation - Mia S. Hagen, M.D; Woody Sorey, B.A; Ermyas Kahsai, B.S; Scott Telfer, Eng.D; Kenneth Chin, M.D; Christopher Y. Kweon, M.D; Albert O. Gee, M.D (Elsevier, 2022)
Purpose: To compare stiffness, strain, and load to failure of 4- versus 5-strand hamstring anterior cruciate ligament reconstruction human tendon allografts with femoral suspensory and tibial interference screw fixation Methods: Allograft hamstring tendons were used to create 10 four-strand (4S) and 10 five-strand (5S) grafts. Grafts were fixed to a uniaxial electromechanical load system via a femoral cortical suspensory button and a bioabsorbable interference screw in bone analogue. Grafts were cycled from 100 Newtons (N) to 250 N for 1,000 repetitions at 0.5 hertz before load to failure testing. Cyclic displacement was defined as the difference in graft length from the first 20 to 30 cycles compared with the last 10 cycles. Trials were recorded on a high-definition camera to allow for digital image correlation analysis. Results: Cyclic displacement more than 1,000 cycles was significantly lower in the 4S compared with the 5S group (0.87 vs 1.11 mm, P = .037). Digital image correlation analysis confirmed that the fifth strand elongated more than the other 4 strands in the 5S constructs (6.1% vs 3.9%, P = .032). Load to failure was greater in the 4S compared with the 5S group but not statistically significant (762 vs 707 N, P = .35). Stiffness was similar between constructs (138.5 vs 138.3 N/mm, P = .96) Conclusions: Compared with cyclically loaded 4S hamstring grafts, the 5S grafts had significantly increased displacement over time in a model of femoral suspensory and tibial interference screw fixation. Clinical Relevance: Anterior cruciate ligament reconstruction with hamstring tendon autograft is a commonly performed surgery with excellent outcomes. It has been shown that graft diameter influences these outcomes. As surgeons use larger grafts, it is important to investigate how these constructs may affect the outcomes of surgery.